The influence of rolling emulsion physical and chemical parameters on the energy consumption of tinplate continuous cold rolling mills - Кухар, В.В.; Кармазіна, І.В.; Присяжний, А.Г. (Problems of Tribology, 2019)
Cold rolling of tinplate is characterized by significant strain on equipment and energy costs, which are a large part of production cost. Decreasing energy costs of tinplate cold rolling is an actual purpose. The choice of rolling emulsion, as the main lever to decrease of friction in the deformation zone, is a decisive move for decreasing energy costs and improving of tinplate quality. Today, in domestic cold rolling shops, the choice of rolling emulsion is based on its lowest cost and consumption per ton of rolled products. This fact limits the ability to solve the most pressing problems: the decreasing of rolling mill strain and roll abrasion; the improvement of rolling process stability, tinplate corrosion resistance and surface quality. Studying the influence of rolling emulsion physical and chemical parameters on the energy consumption of tinplate continuous cold rolling mills will allow choosing rolling emulsion that will decrease of rolling mill strain and energy costs. The purpose of this article is a theoretical research of rolling emulsion kinematic viscosity influence on the energy costs of continuous cold rolling mill. In the course of the research, deformation modes were developed for three types of continuous cold rolling mill: four-, five-, and six-stand. The energy and force parameters of the rolling process were calculated using rolling emulsions with different kinematic viscosity in the range of 16-102.76 m2/s. Rolling emulsions, which were used in the period 2015-2018 at the PJSC Zaporizhstal cold rolling mill, were taken into account for the research the influence of rolling emulsion physical and chemical parameters on the energy consumption of tinplate continuous cold rolling mills. It is defined that increasing the rolling emulsion kinematic viscosity decreases the energy consumption of tinplate continuous cold rolling mills. In addition, the increase in rolling mill strain increases energy savings. It is defined that increasing the rolling emulsion kinematic viscosity by 10 m2/s decreases energy consumption at the four-stand cold rolling mill № 2 (PJSC Zaporizhstal) by 0.07 kJ.h/t (0.82 %); at the five-stand cold rolling mill (Chiba, Japan) – by 5.81 kJ.h/t (1.77 %); at the six-stand cold rolling mill 1400 (ArcelorMittal Temirtau) – by 4.70 kJ.h/t (1.54 %).